The role of autophagy and ferroptosis in sensorineural hearing loss - Sun, Ying; Zou, Shengyu; He, Zuhong; Chen, Xiong (Frontiers in Neuroscience, 2022)
Hearing loss has become a common sensory defect in humans. Because of the limited regenerative ability of mammalian cochlear hair cells (HCs), HC damage (caused by ototoxic drugs, aging, and noise) is the main risk factor of hearing loss. However, how HCs can be protected from these risk factors remains to be investigated. Autophagy is a process by which damaged cytoplasmic components are sequestered into lysosomes for degradation. Ferroptosis is a novel form of non-apoptotic regulated cell death involving intracellular iron overloading and iron-dependent lipid peroxide accumulation. Recent studies have confirmed that autophagy is associated with ferroptosis, and their crosstalk may be the potential therapeutic target for hearing loss. In this review, we provide an overview of the mechanisms of ferroptosis and autophagy as well as their relationship with HC damage, which may provide insights for a new future in the protection of HCs.